Endoglin concentration in peritoneal fluid of patients with endometriosis (Faculty of Medicine Universitas Indonesia, 2013)
Background: Endoglin is a specific angiogenic factor suspected to involve in the pathogenesis of endometriosis. The aim of this study was to evaluate the significance of endoglin concentration in the peritoneal fluid of patients with endometriosis. Methods: This pilot study was performed between March 2011 and July 2012 at Dr. Wahidin Sudirohusodo Hospital and another private hospital in Makassar, Indonesia. This was an observational, cross-sectional study. All patients undergoing laparoscopy for infertility and other cases with suitable inclusion criteria were asked to answer a questionnaire and had a 5 cc peritoneal fluid sample taken for measurement of peritoneal endoglin concentration using ELISA. Endometriosis stage was classified using ASRM criteria and divided into two groups, mild and severe. All data were analyed using Excel and Spearman correlation analysis. Results: In the endometriosis group peritoneal endoglin concentration ranged between 14.43- 15.65 ng/mL (median 15.04 ng/mL) which is higher than control group 7.42-10.26 ng/mL (median 8.84 ng/mL). A peritoneal endoglin concentration equal to or higher than 11 ng/mL could be used to predict endometriosis. Conclusion: Endoglin concentrations increased proportionally with the severity of endometriosis, and many be used as predictive factor of endometriosis cases. (Med J Indones. 2013;22:88-91)